A novel calcium-chelating peptide purified from Auxis thazard protien hydrolysate and its binding properties with calcium. (September 2019) - Chen, Ming; Ji, Hongwu; Zhang, Zewei; Zeng, Xuege; Su, Weiming; Liu, Shucheng
Graphical abstract: Highlights: A novel calcium-binding peptide was isolated from Auxis thazard protein hydrolysate. The sequence of the purified calcium-binding peptide was identified as Glu-Pro-Ala-His. The chelating sites involved the carboxylic groups of Glu as well as the carboxylic group and the amino group of His. Hypothetical molecular model of peptide-calcium chelate was constructed. Abstract: Auxis thazard protein peptides were prepared by enzymatic hydrolysis and membrane separation and then sequentially purified with Sephadex G-15 gel chromatography and reversed phase high performance liquid chromatography (RP-HPLC) based on their calcium binding capacity. A novel peptide purified from Auxis thazard protien peptides exhibited the highest calcium binding activity (76.8 ± 4.5 mg/g) and was identified as Glu-Pro-Ala-His (MW = 453.3 Da). The results of FTIR and mass spectrometry showed that the binding sites of calcium-binding peptide involved the carboxylic group of Glu, as well as the carboxylic group and the amino group of His. A hypothesized molecular model of peptide-calcium chelate was constructed and the difference of the molecular structure and apparent structure of peptide (Glu-Pro-Ala-His) before and after chelating with calcium was also confirmed by scanning electron microscope. These study results indicated that Auxis thazard protein hydrolysate was a high quality source of peptides with calcium binding activity.